PENGARUH PENGGUNAAN MULTIMEDIA PEMBELAJARAN DAN MOTIVASI TERHADAP PRESTASI BELAJAR BAHASA INGGRIS DI SMA 10 PALEMBANG - Violeta Nirmala (Program Magister Manajemen Indo Global Mandiri University, 2020)
The influence the use of multimedia learn and motivation achievement of students in learning English lesson in school district 10 Palembang. Guided by Waspodo and H.Lin Yan Syah. In the process of achieving the goal of learning, the use of multimedia motivation to learn is also a very big role on the interpretation of student learning. Due to the learning motivation in students , thus increasing learning achievement is also high on student achievement. The purpose of the study is to investigate and examine the effect of multimedia learning and motivation against students in achievement learning English lesson in school in school district 10 Palembang. The study also wanted to know and test whether the two exogenous variables from the above that the dominant influence on student achievement in English language subject in school district 10 Palembang. Causal type of research is the research that aims to explain the influence of several variables. The object of the study were students and a sample set a of 60 samples. By using random sampling model analysis was used to prove the hypothesis that use of the Path Analysis Testing (path analysis) with AMOS, USING Structural Equation Model (SEM). SEM results with the value of CR (Critical Ratio) of-0 082 for multimedia on learning achievement and 8595 for Achievement Motivation Learning to learn, with CR Values > 1671 CR means of two values which are able to explain and a strong influence on the variable endogenous variable is the motivation to learn. Where multimedia effect on motivation to learn is casually with the CR 3297